THEORIES OF PERSONALITY STUDY IN PSYCHOLOGY - Yusufova Farangiz (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This thesis examines the main theories of personality study in psychology and their scientific significance in understanding human behavior and mental development. The paper analyzes psychoanalytic, behaviorist, humanistic, cognitive and trait theories of personality. The views of famous psychologists on the formation, development and manifestation of personality are discussed. The importance of personality theories in modern psychology, education and social life is also highlighted. The thesis explains how personality theories help to understand individual differences, motivation, emotions and human relationships.